Agama dan Pembentukan Karakter Generasi Alfa di Era Postdigital - Sakoan, Siskawaty (JURNAL TERUNA BHAKTI, 2024)
Generation Alfa is a demographic group that follows Generation Z, a generation (born 2010-onwards) growing up in an all-digital world and facing significant challenges in character formation. The phenomenon of gadget addiction and lack of social interaction in children raises concerns about hampering their emotional and spiritual development. Religion and the development of digital technology have an essential role in shaping the character of Generation Alfa. The digital era has significantly impacted how Generation Alfa understands values, ethics, and social interactions. As a moral and ethical filter, religion also influences this generation's character formation. This article aims to explain the role of religion in shaping the character of alpha-generation children to control digital addiction and strengthen their social-emotional intelligence. This research uses qualitative methods and a literature review approach. Where researchers collect data and information regarding character formation in the postdigital era in early childhood, sourced from various research journals, both national and international, magazines, various supporting books, and newspapers. This research shows that religious education plays a vital role in shaping the children's character of the digital generation by instilling empathy, caring, and responsibility as wise, intelligent, and ethical digital filters. Abstrak Generasi Alfa adalah kelompok demografi yang mengikuti generasi Z, generasi yang (lahir 2010-seterusnya) tumbuh besar dalam dunia serba digital dan menghadapi tantangan besar dalam pembentukan karakter. Fenomena kecanduan gadget dan kurangnya interaksi sosial pada anak menimbulkan kekhawatiran akan terhambatnya perkembangan emosi dan spiritual mereka. Agama dan perkembangan teknologi digital memiliki peran penting dalam membentuk karakter Generasi Alfa. Era digital membawa dampak signifikan terhadap cara Generasi Alfa memahami nilai, etika, dan interaksi sosial. Agama, sebagai filter moral dan etika, turut memengaruhi pembentukan karakter generasi ini. Tulisan ini bertujuan menguraikan peran agama dalam dalam membentuk karakter anak generasi alpha untuk mengendalikan kecanduan digital dan menguatkan kecerdasan sosial-emosi mereka. Penelitian ini menggunakan metode kualitatif dengan menggunakan pendekatan literature review. Dimana peneliti melakukan pengumpulan data dan informasi mengenai pembentukan karakter di era postdigital pada anak usia dini yang bersumber dari berbagai jurnal penelitian baik nasional maupun internasional, majalah, berbagai buku penunjang maupun surat kabar. Hasil penelitian ini menunjukkan bahwa Pendidikan agama berperan penting membentuk karakter anak generasi digital melalui penanaman nilai empati, kepedulian, dan tanggung jawab sebagai filter digital yang bijak, cerdas, dan beretika.